2013
DOI: 10.3168/jds.2012-5451
|View full text |Cite
|
Sign up to set email alerts
|

Performance of dairy cows fed high levels of acetic acid or ethanol

Abstract: Ethanol and acetic acid are common end products from silages. The main objective of this study was to determine whether high concentrations of ethanol or acetic acid in total mixed ration would affect performance in dairy cows. Thirty mid-lactation Holstein cows were grouped in 10 blocks and fed one of the following diets for 7 wk: (1) control (33% Bermuda hay + 67% concentrates), (2) ethanol [control diet + 5% ethanol, dry matter (DM) basis], or (3) acetic acid (control diet + 5% acetic acid, DM basis). Ethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1
12

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 36 publications
5
39
1
12
Order By: Relevance
“…At least ethanol does not seem to impact preference negatively, which supports previous studies (Daniel et al, 2013;Randby et al, 1999) with dairy cows. Besides significant reductions in preference and DMI, volatilization of ethanol and methanol during aerobic exposure adds losses of energy to the silage DM.…”
Section: Animal Preference and Dry Matter Intakesupporting
confidence: 89%
See 1 more Smart Citation
“…At least ethanol does not seem to impact preference negatively, which supports previous studies (Daniel et al, 2013;Randby et al, 1999) with dairy cows. Besides significant reductions in preference and DMI, volatilization of ethanol and methanol during aerobic exposure adds losses of energy to the silage DM.…”
Section: Animal Preference and Dry Matter Intakesupporting
confidence: 89%
“…This might be caused by oxidation by aerobic microorganisms but could be more likely a result of volatilization (Daniel et al, 2013). A stronger heating on d8 was observed in TRE despite a better hygienic quality at opening.…”
Section: Silage Quality and Changes During Aerobic Exposurementioning
confidence: 96%
“…Notwithstanding, acetic acid concentration was low and similar across treatments (13.0 and 13.8 g/kg for the control and inoculated silages, respectively), with no interference on animal performance. Previous studies reported a clear negative effect of acetic acid on feeding behavior, but the dietary concentrations of acetic acid were higher than those found in the present trial (Dinius et al, 1968;Hutchinson and Wilkins, 1971;Krizsan et al, 2012;Daniel et al, 2013).…”
Section: Itemcontrasting
confidence: 54%
“…Therefore, ensiling sugarcane results in the conversion of most of the SC into fermentation end-products, which are characterized by high levels of volatile organic compounds, primarily ethanol (Kung and Stanley, 1982;Pedroso et al, 2005;Daniel et al, 2013b). Although the gross energy is almost completely recovered during alcoholic fermentation (McDonald et al, 1991), large amounts of DM and net energy are lost (Daniel and Nussio, 2011;Daniel et al, 2013a). Because of the undesirable characteristics of natural fermentation in sugarcane silages, there is a need to identify additives that can inhibit epiphytic yeast populations, and mitigate nutrient losses (Ávila et al, 2014).…”
Section: Introductionmentioning
confidence: 97%